Anthropologies : a family memoir - Alvarado, Beth (Sightline books., 2011)
A vivid archive of memories, Beth Alvarado & rsquo;s Anthropologies layers scenes, portraits, dreams, and narratives in a dynamic cross-cultural mosaic. Bringing her lyrical tenor to bear on stories as diverse as harboring teen runaways, gunfights with federales, and improbable love, Alvarado unveils the ways in which seemingly separate moments coalesce to forge a communal truth. Woven from the threads of distinct family histories and ethnic identities, Anthropologies creates a heightened understanding of how individual experiences are part of a larger shared fabric of lives.℗¡Like the opening of.